Interconnection scheme of VxLAN based cloud datacenter networks - Jiexin ZHANG; Zhiming WU (Dianxin kexue)
Several interconnection and interworking schemes of cloud datacenter networks based on VxLAN technique were studied in prospective of VxLAN technique and underlay network status. And the respective advantages and disadvantages of these schemes were analyzed. Finally, the applicable scenarios of each scheme were summarized. It is in the hope that the study would provide some useful technique references for the development of carriers'datacenters.